COP27: financing pledges and managing expectations - Sembiring, Margareth (2023)
The aim of Egypt’s chairmanship of the latest climate change conference was on the implementation of financing pledges to realise specific goals for mitigating the climate crisis. Yet, limited success was achieved. Going forward, it is necessary to manage expectations and to redirect efforts into what is deliverable.